Answer: for 6(x + 2) - x = 4(x + 4) + 7, x = 11
For 0.8x + 5 = 0.2(40 - x), x = 3
For x = 3
For 5(x - 1) - 6x = - 11x
x = 1/2
Explanation:
1)Looking at the first equation,
6(x + 2) - x = 4(x + 4) + 7
6x + 12 - x = 4x + 16 + 7
6x - x - 4x = 16 + 7 - 12
x = 11
2) 0.8x + 5 = 0.2(40 - x)
0.8x + 5 = 8 - 0.2x
Adding 0.2x to the left hand side and the right hand side of the equation, it becomes
0.8x + 0.2x + 5 = 8 - 0.2x + 0.2x
x + 5 = 8
x = 8 - 5 = 3
3) 5(x - 1) - 6x = - 11x
5x - 5 - 6x = - 11x
5x - 6x = - 11x + 5
- x + 11x = 5
10x = 5
x = 5/10 = 1/2